2016
DOI: 10.1590/s1678-9946201658001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biofilm Formation in Coagulase-Negative Staphylococci Isolated From Platelet Concentrate Bags

Abstract: Platelet Concentrates (PCs) are the blood components with the highest rate of bacterial contamination, and coagulase-negative staphylococci (CoNS) are the most frequently isolated contaminants. This study investigated the biofilm formation of 16 contaminated units out of 691 PCs tested by phenotypic and genotypic methods. Adhesion in Borosilicate Tube (ABT) and Congo Red Agar (CRA) tests were used to assess the presence of biofilm. The presence of icaADC genes was assessed by means of the Polymerase Chain Reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
3
5
2
Order By: Relevance
“…Being on non-invasive ventilation (NIV) was also associated with higher hazard of mortality (AHR: 2.99 [1.24, 7.28]). This finding is in line with studies conducted in Uganda [13], Mexico [33] and Brazil [34]. The possible explanation could be that most of patients in this study were at an advanced stage of the disease and they tended to be critically ill with multiorgan failure during admission.…”
Section: Discussionsupporting
confidence: 92%
“…Being on non-invasive ventilation (NIV) was also associated with higher hazard of mortality (AHR: 2.99 [1.24, 7.28]). This finding is in line with studies conducted in Uganda [13], Mexico [33] and Brazil [34]. The possible explanation could be that most of patients in this study were at an advanced stage of the disease and they tended to be critically ill with multiorgan failure during admission.…”
Section: Discussionsupporting
confidence: 92%
“…We found that 90.8% of MR-CoNS isolated in this study were biofilm producer tested by the CRA method. This result was higher than the findings reported by Martini et al (2016) , which found that 43.75% biofilm producer of all CoNS isolated form platelet concentrates bags [ 28 ]. Oliveira and Cunha reported that 75% of clinical staphylococci isolates were biofilm positive determined by CRA method [ 29 ].…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies conducted in the city of Diamantina have shown that the same intestinal parasites are also circulating in schools and buses. 16 , 17 It is noticed that the biological forms of these parasites are circulating in the most diverse environments and so it is necessary to establish public health policies and to encourage healthy habits. Thus, avoiding the transmission of these agents.…”
Section: Discussionmentioning
confidence: 99%